Complete Genome Sequence of the Type Strain Tepidimonas taiwanensis LMG 22826T, a Thermophilic Alkaline Protease and Polyhydroxyalkanoate Producer - Heřmánková, Kristýna; Kouřilová, Xenie; Buchtíková, Iva; Bezdíček, Matěj; Lengerová, Martina; Obruča, Stanislav; Sedlář, Karel (Oxford University Press, 2021)
Tepidimonas taiwanensis is a moderately thermophilic, Gram-negative, rod-shaped, chemoorganoheterotrophic, motile bacterium. The alkaline protease producing type strain Tepidimonas taiwanensis LMG 22826T was recently reported to also be a promising producer of polyhydroxyalkanoates (PHAs) – renewable and biodegradable polymers representing an alternative to conventional plastics. Here, we present its first complete genome sequence which is also the first complete genome sequence of the whole species. The genome consists of a single 2,915,587bp long circular chromosome with GC content of 68.75%. Genome annotation identified 2,764 genes in total while 2,634 open reading frames belonged to protein-coding genes. Although functional annotation of the genome and division of genes into Clusters of Orthologous Groups (COGs) revealed a relatively high number of 694 genes with unknown function or unknown COG, the majority of genes were assigned a function. Most of the genes, 406 in total, were involved in energy production and conversion, and amino acid transport and metabolism. Moreover, particular key genes involved in the metabolism of PHA were identified. Knowledge of the genome in connection with the recently reported ability to produce bioplastics from the waste stream of wine production makes T. taiwanensis LMG 22826T an ideal candidate for further genome engineering as a bacterium with high biotechnological potential.

Tepidimonas taiwanensis is a moderately thermophilic, Gram-negative, rod-shaped, chemoorganoheterotrophic, motile bacterium. The alkaline protease producing type strain Tepidimonas taiwanensis LMG 22826T was recently reported to also be a promising producer of polyhydroxyalkanoates (PHAs) – renewable and biodegradable polymers representing an alternative to conventional plastics. Here, we present its first complete genome sequence which is also the first complete genome sequence of the whole species. The genome consists of a single 2,915,587bp long circular chromosome with GC content of 68.75%. Genome annotation identified 2,764 genes in total while 2,634 open reading frames belonged to protein-coding genes. Although functional annotation of the genome and division of genes into Clusters of Orthologous Groups (COGs) revealed a relatively high number of 694 genes with unknown function or unknown COG, the majority of genes were assigned a function. Most of the genes, 406 in total, were involved in energy production and conversion, and amino acid transport and metabolism. Moreover, particular key genes involved in the metabolism of PHA were identified. Knowledge of the genome in connection with the recently reported ability to produce bioplastics from the waste stream of wine production makes T. taiwanensis LMG 22826T an ideal candidate for further genome engineering as a bacterium with high biotechnological potential.
Complete Genome Sequence of the Type Strain Tepidimonas taiwanensis LMG 22826T, a Thermophilic Alkaline Protease and Polyhydroxyalkanoate Producer
Keywords: Tepidimonas taiwanensis; polyhydroxyalkanoates; hybrid assembly; Oxford Nanopore Technologies; functional annotation; alkaline protease; Tepidimonas taiwanensis; polyhydroxyalkanoates; hybrid assembly; Oxford Nanopore Technologies; functional annotation; alkaline protease